Research on college counselors' work innovation from the new media perspective - Ma, Qinjuan; Wang, Pingshui (IJRDO - Journal of Social Science and Humanities Research, 2018)
Informationization of college student work should be should effectively meet the needs of students in terms of platform construction, resource integration and the use of new media technology. Encouraging counselors to actively participate in information construction is conducive to maximizing the satisfaction of students' information needs and promoting the realization of the goal of students' development. Improving the information literacy of counselors and promoting the innovation of information work of counselors are the important contents and requirements of information construction and education quality improvement in colleges and universities.